2019
DOI: 10.1002/mnfr.201801014
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Protects Against Alcohol‐Induced Liver Cell Injury Within an NRF2–ALDH2 Feedback Loop

Abstract: Scope Alcoholic liver disease (ALD) is a major cause of morbidity and mortality worldwide. Oxidative stress induced during the alcohol metabolism plays a crucial role in ALD, and clinical evidence demonstrates the prevalence and risks of vitamin D (VD) deficiency in ALD. This study aims to explore the mechanism of VD administration to ameliorate alcohol‐induced cell injury. Methods and results VD activates NRF2 (nuclear factor erythroid 2 (NF‐E2)‐related factor 2) signals along with upregulation of ALDH2 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
3
15
0
Order By: Relevance
“…Meanwhile, calcitriol also triggered Nrf2 signaling, inducing the expression of targeted genes and protecting the brain from excessive oxidative stress. In support of our ndings, recent studies also illustrate a pivotal role of Nrf2 in the protective effects of VitD in Alzheimer's disease, lung injury, skin aging, liver failure and kidney toxicity (21)(22)(23)(24)(25). Given that Keap-1 is targeted to autophagosomes for degradation, the reduction of Keap-1 expression and the decreased co-expression of p62 and Keap1 following calcitriol treatment suggest that Nrf2 might be activated by VitD through autophagy mediated by the interaction between p62 and Keap1.…”
Section: Discussionsupporting
confidence: 83%
“…Meanwhile, calcitriol also triggered Nrf2 signaling, inducing the expression of targeted genes and protecting the brain from excessive oxidative stress. In support of our ndings, recent studies also illustrate a pivotal role of Nrf2 in the protective effects of VitD in Alzheimer's disease, lung injury, skin aging, liver failure and kidney toxicity (21)(22)(23)(24)(25). Given that Keap-1 is targeted to autophagosomes for degradation, the reduction of Keap-1 expression and the decreased co-expression of p62 and Keap1 following calcitriol treatment suggest that Nrf2 might be activated by VitD through autophagy mediated by the interaction between p62 and Keap1.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, a recent study reported that vitamin D attenuated alcohol-induced HepG2 cell injury partially by upregulating ALDH2 expression [23]. One possible explanation for this discrepancy could be that in our study, we only focus our attention on the activity of ALDH.…”
Section: Discussionmentioning
confidence: 70%
“…CBRs are NAPDH‐dependent enzymes involved in the protection of cell against lipid peroxidation by reducing various endogenous carbonyl compounds including 4‐oxonon‐2‐enal (ONE), 4‐hydroxynon‐2‐enal (HNE) and acrolein (Huang et al, ). Alcohol dehydrogenase (ADH3) and Aldehyde dehydrogenase (ALDH)Both these enzymes are crucial in the detoxification process in case of ethanol‐induced stress and are reported to be downstream targets of Nrf2 signaling (Wu et al, ). Ethanol is metabolized to form toxic acetaldehyde by alcohol dehydrogenase (ADH), which in turn is transformed into nontoxic acetate by aldehyde dehydrogenase (ALDH) (Zhang, Xue, Li, Zhang, & Tao, ). Apart from the above‐mentioned function, ADH is also assigned to GSH‐mediated detoxification of formaldehyde that is formed as a by‐product of oxidative demethylation of histones and during degradation of creatinine and betaine (Goto et al, ).…”
Section: Downstream Target Proteins Of Nrf2mentioning
confidence: 99%